Silicon-based negative electrode material and preparation method and application thereof

By constructing the three-dimensional crosslinking network structure of silicon-based anode material and optimizing the SEI layer interface, the problems of volume expansion and electrochemical kinetics of silicon materials in lithium-ion batteries are solved, and high specific capacity and excellent cycling performance are achieved.

CN120511267AActive Publication Date: 2025-08-19CENT SOUTH UNIV

Patent Information

Application Number
CN202510665252.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-08-19
Estimated Expiration
2045-05-22

AI Technical Summary

Technical Problem

When silicon material is used as the negative electrode of a lithium-ion battery, there are problems such as volume expansion, poor electrode contact, instability of SEI, poor electrochemical kinetics, slow charge transfer and low initial Coulomb efficiency, which limits its application in lithium-ion batteries.

Method used

Using a silicon-based negative electrode material with a mass ratio of 0.5-1:8.4 of slurry to copper sheet, the slurry includes silicon powder, sodium alginate, the conductive agent poly(3,4-ethylenedioxythiophene)/polystyrene sulfonic acid, initiator and solvent, the mechanical stability and conductivity are enhanced by constructing a three-dimensional crosslinking network structure and optimizing the self-healing SEI layer interface.

Benefits of technology

It significantly improves the specific capacity and circulation performance of lithium-ion batteries, suppresses volume expansion, maintains the structural integrity of the silicon negative electrode, and improves the circulation stability and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120511267A_ABST
    Figure CN120511267A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a silicon-based negative electrode material and a preparation method and application thereof. The silicon-based negative electrode material comprises slurry and a copper sheet, and the mass ratio of the slurry to the copper sheet is (0.5-1): 8.4; the slurry is prepared from silicon powder, sodium alginate, a conductive agent, poly (3, 4-ethylenedioxythiophene) / polystyrolsulfon acid, an initiator and a solvent; the initiator is a polar solvent. The structural stability of the silicon-based negative electrode material in the lithiation / delithiation process is realized by constructing a three-dimensional (3D) cross-linked network structure on the surface of the silicon particles and optimizing a self-repairing SEI layer interface. And the network structure can effectively inhibit volume expansion of the silicon negative electrode material and maintain the integrity of the silicon negative electrode morphology, so that the specific capacity and the cycle performance of the lithium ion battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a silicon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] While silicon materials possess high specific capacity when used as anodes in lithium-ion batteries, they experience volume expansion during battery cycling, hindering their further application in these batteries. On the one hand, the significant volume changes experienced by silicon materials during cycling can lead to severe particle pulverization and poor electrode contact. This volume change leads to an unstable solid electrolyte interface (SEI), which repeatedly breaks and regenerates on the electrode surface, continuously consuming electrolyte and active lithium. These issues significantly reduce the cycling performance of lithium-ion batteries. On the other hand, silicon's low conductivity and the thin oxide layer formed on silicon particles lead to poor electrochemical kinetics during alloying and dealloying, slowing charge transfer and exacerbating polarization, limiting rate performance. Furthermore, these low kinetics may prevent some lithium from being fully released during the first charge, resulting in low initial coulombic efficiency (ICE) and irreversible capacity loss. Therefore, to further enhance the application of silicon materials in lithium-ion batteries, a silicon anode material with low volume change during cycling is urgently needed. Summary of the Invention

[0003] The present invention aims to provide a silicon-based negative electrode material, comprising a slurry and a copper sheet, wherein the mass ratio of the slurry to the copper sheet is 0.5-1:8.4;

[0004] The slurry comprises: silicon powder, sodium alginate, a conductive agent, poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, an initiator and a solvent;

[0005] The initiator is a polar solvent.

[0006] Preferably, the mass volume ratio of the silicon powder, sodium alginate, conductive agent, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, initiator and solvent is 7-8 g: 1-2 g: 1 g: 920-960 μL: 230-240 μL: 70-115 mL.

[0007] Preferably, the thickness of the copper sheet is 18-22 mm, and the particle size of the silicon powder is 25-35 nm.

[0008] Preferably, the conductive agent is a carbon black conductive agent.

[0009] Preferably, the polar solvent includes one or more of ethanol, ethylene glycol and isopropanol.

[0010] Preferably, the solvent comprises water and / or ethanol.

[0011] The present invention also provides a method for preparing the silicon-based negative electrode material, comprising the following steps:

[0012] (1) mixing silicon powder, sodium alginate, a conductive agent, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid), an initiator, and a solvent to obtain a slurry;

[0013] (2) The slurry is applied on a copper foil and dried to obtain the silicon-based negative electrode material.

[0014] Preferably, the mixing temperature in step (1) is 24-26° C., and the mixing time is 2-5 min.

[0015] Preferably, the drying temperature is 140-160° C., and the drying time is 2.5-3.5 hours.

[0016] The present invention also provides the use of the above-mentioned silicon-based negative electrode material or the silicon-based negative electrode material prepared by the above-mentioned method for preparing the silicon-based negative electrode material in lithium-ion batteries.

[0017] The present invention has the following beneficial effects:

[0018] The present invention provides a silicon-based negative electrode material, comprising a slurry and a copper sheet, wherein the mass ratio of the slurry to the copper sheet is 0.5-1:8.4; the slurry comprises silicon powder, sodium alginate, a conductive agent, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, an initiator, and a solvent; the initiator is a polar solvent. The present invention uses poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid (PEDOT:PSS) as a water-soluble conductive polymer and adds it to the slurry system. The sulfonic acid groups (-SO3H) in its molecular structure can be protonated to hydroxyl groups (-OH) in an acidic medium, and then interact with the silanol groups (Si-OH) on the surface of the silicon powder through hydrogen bonding to form a stable interfacial connection, effectively buffering the volume deformation of the silicon negative electrode material during the charge and discharge of lithium-ion batteries, and maintaining the integrity of the silicon-based negative electrode structure.

[0019] Using polar solvents as initiators, under thermal initiation conditions, the PEDOT chain segments in poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid can undergo intramolecular conformational reorganization, transforming from a benzene structure to a quinone structure, significantly improving its π-π conjugation degree, thereby enhancing the conductivity of the system.

[0020] Sodium alginate (SA) has a high density of evenly distributed carboxyl (-COOH) functional groups in its molecular structure. Compared to carboxymethyl cellulose (CMC), it not only exhibits higher viscoelasticity and mechanical strength, but also forms stronger chemical bonds with the surface of silicon powder. The carboxyl groups in sodium alginate can undergo an esterification reaction with the hydroxyl groups (Si-OH) on the surface of silicon powder to form a stable ester bond (-COO-Si-), thereby effectively suppressing the volume expansion effect of the silicon negative electrode material during the charge and discharge process of lithium-ion batteries.

[0021] Sodium alginate, silicon powder, and poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid can interact through ester bonds or hydrogen bonds to synergistically construct a three-dimensional (3D) cross-linked network structure. This network structure not only gives the silicon negative electrode material excellent mechanical stability, but also increases the effective contact area between the active material-conductive agent-current collector. During the lithium-ion battery cycle, the integrity of the silicon negative electrode material structure is maintained through a dynamic self-repairing mechanism, which inhibits problems such as active material stripping and excessive growth of the solid electrolyte interface (SEI) film, and promotes the formation of a uniform and stable solid electrolyte interface (SEI) film. This stable solid electrolyte interface can significantly improve the lithium ion transfer kinetics and reduce the interfacial impedance, thereby effectively improving the cycle stability and rate performance of the lithium-ion battery.

[0022] By constructing a three-dimensional (3D) cross-linked network structure on the surface of silicon particles and optimizing the self-healing SEI layer interface, the present invention achieves structural stability of silicon-based anode materials during lithiation / delithiation processes. This network structure also effectively inhibits the volume expansion of the silicon anode material, maintaining the integrity of the silicon anode morphology, thereby significantly improving the specific capacity and cycle performance of lithium-ion batteries.

[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a SEM image of the silicon-based negative electrode material prepared in Example 1 of the present invention;

[0025] Figure 2 is a SEM image of the silicon-based negative electrode material prepared in Comparative Example 1 of the present invention;

[0026] Figure 3 1 is a comparison chart of XRD patterns of silicon-based negative electrode materials prepared in Example 1 of the present invention and in Comparative Example 1;

[0027] Figure 4 is a GCD curve diagram of the lithium-ion battery assembled in Application Example 1 of the present invention;

[0028] Figure 5 is a GCD curve diagram of the lithium-ion battery assembled in Application Example 2 of the present invention;

[0029] Figure 6 This is a comparison chart of the cycle performance tests of lithium-ion batteries assembled in Application Example 1 and Application Example 2 of the present invention;

[0030] Figure 7 This is a rate performance test chart of the lithium-ion battery prepared in Application Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described below with reference to the accompanying drawings and examples. Unless otherwise defined, technical or scientific terms used herein shall have the same meanings as those commonly understood by persons of ordinary skill in the art to which the present invention pertains. The above-mentioned features or features described in the specific examples of the present invention may be combined in any manner. These specific examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention.

[0032] The present invention provides a silicon-based negative electrode material, comprising a slurry and a copper sheet, wherein the mass ratio of the slurry to the copper sheet is 0.5-1:8.4;

[0033] The slurry comprises: silicon powder, sodium alginate, a conductive agent, poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, an initiator and a solvent;

[0034] The initiator is a polar solvent.

[0035] In some embodiments of the present invention, the mass volume ratio of the silicon powder, sodium alginate, conductive agent, poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, initiator and solvent is 7-8g: 1-2g: 1g: 920-960μL: 230-240μL: 70-115mL.

[0036] In some embodiments of the present invention, the thickness of the copper sheet is 18-22 mm, and the particle size of the silicon powder is 25-35 nm.

[0037] In some embodiments of the present invention, the conductive agent is a carbon black conductive agent.

[0038] In some embodiments of the present invention, the carbon black conductive agent includes one or more of Super P, Ketjen black, and acetylene black.

[0039] In some embodiments of the present invention, the solid content of the poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid is 1.3-1.7 wt %.

[0040] In some embodiments of the present invention, the polar solvent includes one or more of ethanol, ethylene glycol, and isopropanol.

[0041] In some embodiments of the present invention, the solvent comprises water and / or ethanol.

[0042] The present invention also provides a method for preparing the silicon-based negative electrode material, comprising the following steps:

[0043] (1) mixing silicon powder, sodium alginate, a conductive agent, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid), an initiator, and a solvent to obtain a slurry;

[0044] (2) The slurry is applied on a copper foil and dried to obtain the silicon-based negative electrode material.

[0045] In some embodiments of the present invention, the specific process of mixing in step (1) includes: grinding the silicon powder, adding sodium alginate, continuing to grind, then adding a conductive agent, continuing to grind to obtain a ground material, adding poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, an initiator and a solvent to the ground material, and mixing.

[0046] In some embodiments of the present invention, the mixing temperature in step (1) is 24-26° C., and the mixing time is 2-5 min.

[0047] In some embodiments of the present invention, the drying temperature is 140-160° C., and the drying time is 2.5-3.5 hours.

[0048] The present invention also provides the use of the above-mentioned silicon-based negative electrode material or the silicon-based negative electrode material prepared by the above-mentioned method for preparing the silicon-based negative electrode material in lithium-ion batteries.

[0049] Example 1

[0050] (1) After grinding 0.15 g of silicon powder with a particle size of 30 nm for 20 min, 0.0188 g of sodium alginate was added and grinding was continued for 10 min. Subsequently, 0.0188 g of SuperP (conductive agent) was added and grinding was continued for 10 min to obtain a ground material. 20 μL of poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid with a solid content of 1.5 wt%, 5 μL of isopropyl alcohol (initiator) and 2 mL of water (solvent) were added to the ground material, and mixed at a temperature of 25°C for 2 min to obtain a slurry.

[0051] (2) 0.6 g of the above slurry was evenly coated on a copper foil with a thickness of 20 mm and a mass of 8.4 g, and then dried in an oven at a temperature of 150° C. for 3 h to obtain a silicon-based negative electrode material.

[0052] Example 2

[0053] (1) After grinding 0.15 g of silicon powder with a particle size of 25 nm for 18 min, 0.0188 g of sodium alginate was added and grinding continued for 8 min. Subsequently, 0.0188 g of Ketjen black (conductive agent) was added and grinding continued for 12 min to obtain a ground material. 20 μL of poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid with a solid content of 1.3 wt%, 5 μL of ethanol (initiator) and 2 mL of water (solvent) were added to the ground material, and the mixture was mixed at 24°C for 4 min to obtain a slurry.

[0054] (2) Take 1 g of the above slurry and evenly coat it on a copper foil with a thickness of 20 mm and a mass of 8.4 g, and then dry it in an oven at a temperature of 160° C. for 2.5 h to obtain a silicon-based negative electrode material.

[0055] Example 3

[0056] (1) After grinding 0.15 g of silicon powder with a particle size of 35 nm for 22 min, 0.0188 g of sodium alginate was added and grinding was continued for 12 min. Subsequently, 0.0188 g of acetylene black (conductive agent) was added and grinding was continued for 12 min to obtain a ground material. 20 μL of poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid with a solid content of 1.7 wt%, 5 μL of ethylene glycol (initiator) and 2 mL of ethanol (solvent) were added to the ground material, and the mixture was mixed at 26°C for 5 min to obtain a slurry.

[0057] (2) Take 0.5 g of the above slurry and evenly apply it on a copper foil with a thickness of 20 mm and a mass of 8.4 g, and then dry it in an oven at a temperature of 140° C. for 3.5 h to obtain a silicon-based negative electrode material.

[0058] Comparative Example 1

[0059] 0.15 g of silicon powder with a particle size of 30 nm was ground for 20 minutes, and then 0.0188 g of polyacrylic acid (PAA) was added and grinding was continued for 10 minutes. Subsequently, 0.0188 g of SuperP (conductive agent) was added and grinding was continued for 10 minutes to obtain a ground material.

[0060] 0.6 g of the above-mentioned ground material was evenly coated on a copper foil with a thickness of 20 mm and a mass of 8.4 g, and then dried in an oven at a temperature of 150° C. for 3 h to obtain a silicon-based negative electrode material.

[0061] Characterization testing

[0062] The silicon-based negative electrode materials prepared in Example 1 and Comparative Example 1 were observed using a scanning electron microscope. Figure 1 and Figure 2 As shown. Figure 1It can be seen that the silicon-based negative electrode material prepared in Example 1 has uniformly distributed silicon powder, and poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid and sodium alginate form a uniform composite coating on the surface of the silicon powder particles. The carboxyl groups on the sodium alginate molecular chain form ester groups with the hydroxyl groups of the silicon surface oxide layer to achieve complete coating. The composite coating constructed by the two can provide mechanical buffering for the silicon powder, while also forming a continuous conductive path on the surface of the silicon negative electrode. This structure effectively suppresses the problem of volume expansion of the silicon-based negative electrode during the cycle of the lithium-ion battery, while ensuring excellent charge transfer performance. According to Figure 2 It can be seen that SuperP (conductive agent) is obviously aggregated around the silicon powder, and part of the silicon powder is directly exposed outside the polyacrylic acid (binder) and the conductive agent.

[0063] The silicon-based negative electrode materials prepared in Example 1 and Comparative Example 1 were subjected to X-ray diffraction analysis, and the results were as follows: Figure 3 As shown. Figure 3 It can be seen that the silicon-based anode material prepared in Example 1 has three distinct high peaks and four weak low peaks. The three high peaks correspond to the Cu PDF#04-0836 card, and the four weak low peaks correspond to the Si PDF#03-0517 card, corresponding to four different crystal planes of silicon. Compared with Example 1, the silicon-based anode material prepared in Comparative Example 1 does not show obvious diffraction peak shifts or the appearance of new diffraction peaks.

[0064] Application Example 1

[0065] The silicon-based negative electrode material prepared in Example 1 was used as the negative electrode of a lithium-ion battery, a high-purity lithium sheet was used as the positive electrode, and a mixed system of ethylene carbonate, dimethyl carbonate, and diethyl carbonate (volume ratio of 1:1:1) was used as the electrolyte. At the same time, lithium hexafluorophosphate and fluoroethylene carbonate were added to the electrolyte (the concentration of lithium hexafluorophosphate in the electrolyte was 1 mol / L, and the mass concentration of fluoroethylene carbonate in the electrolyte was 5%). The dosage of the electrolyte used for a single battery was 90 μL. The battery was assembled in an argon-protected glove box (H2O<0.01ppm, O2<0.01ppm), a polypropylene separator with a diameter of 19 mm (Celgard 2400) was placed, and a CR2032 lithium-ion battery was assembled.

[0066] Application Example 2

[0067] The assembly steps of the lithium ion battery are the same as those of Application Example 1, except that the silicon-based negative electrode material prepared in Comparative Example 1 is used as the negative electrode of the lithium ion battery.

[0068] Electrochemical performance test

[0069] The lithium-ion battery prepared in Example 1 was subjected to constant current charge and discharge test at a current density of 0.2 A / g, and the obtained GCD curve was as follows: Figure 4 As shown. Figure 4 It can be seen that when the silicon-based negative electrode sheet prepared in Example 1 of the present invention is used as the negative electrode material of the lithium-ion battery, the first coulombic efficiency of the lithium-ion battery reaches 91.76%, and the first discharge specific capacity is as high as 3256.65 mAh / g, indicating that its interface side reactions are effectively suppressed, forming a relatively stable interface and conductive network structure.

[0070] The lithium-ion battery prepared in Example 2 was subjected to constant current charge and discharge tests at a current density of 0.2 A / g, and its GCD curve is shown in FIG. Figure 5 As shown. Figure 5 It can be seen that when the silicon-based negative electrode sheet prepared in Comparative Example 1 is used as the negative electrode material for a lithium-ion battery, the initial coulombic efficiency of the lithium-ion battery is only 82.4%, far lower than that of Application Example 1 of the present invention (91.76%), and the initial discharge specific capacity is 3495.9 mAh / g. This shows that using polyacrylic acid alone as a binder is difficult to form a stable solid electrolyte interface (SEI) film, cannot effectively alleviate the volume change of the silicon negative electrode material during the lithium insertion / extraction process, and is insufficient to maintain the structural integrity of the silicon negative electrode material, resulting in contact failure between the active material and the current collector.

[0071] The lithium ion batteries prepared in Example 1 and Example 2 were subjected to cycle performance tests at a current density of 1 A / g. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that when the number of cycles of the lithium-ion battery prepared in Application Example 1 reaches 70, the capacity retention rate is 76.02%, and the average coulombic efficiency is as high as 99.2%, which fully proves that the silicon-based negative electrode material prepared in Example 1 of the present invention has excellent structural stability. In contrast, the lithium-ion battery prepared in Application Example 2 has a cycle life of less than 40 times under the same test conditions, showing a rapid attenuation trend and a significantly reduced capacity retention rate. This shows that the silicon-based negative electrode material prepared in Example 1 of the present invention has a stable cross-linked structure, which alleviates the problems of electrode pulverization and capacity attenuation caused by volume changes in traditional silicon-based negative electrode materials.

[0072] The lithium-ion battery prepared in Example 1 was tested for rate performance. The results are as follows: Figure 7 As shown. Figure 7 As can be seen, at a high rate of 1C (1C = 4A / g), the electrode material still maintains a reversible capacity of 1255mAh / g; when the rate returns to 0.05C, the specific capacity can be restored to 3000mAh / g, with a capacity recovery rate of 81.54%. This demonstrates that the silicon anode material provided by the present invention has a stable electrode structure, and the synergistic effect of Si-OC covalent bonds and hydrogen bonds ensures the structural integrity of the material during lithium ion insertion and extraction.

[0073] Therefore, the present invention provides a silicon-based negative electrode material that effectively solves the problem of volume change of silicon-based negative electrode materials during lithium battery cycling through multiple interactions such as hydrogen bonding, chemical bonding, and physical crosslinking between poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid (PEDOT:PSS), sodium alginate (SA), and silicon powder. Experiments have shown that when the silicon-based negative electrode material of the present invention is used in the negative electrode of a lithium-ion battery, the lithium-ion battery has an initial coulombic efficiency of 91.76%, a platform capacity of 2200mAh / g at a current density of 1.0A / g, and a capacity retention rate of 76.02% after 70 stable cycles.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A silicon-based negative electrode material, characterized in that: The method comprises a slurry and a copper sheet, wherein the mass ratio of the slurry to the copper sheet is 0.5-1:8.4; The slurry comprises: silicon powder, sodium alginate, a conductive agent, poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, an initiator and a solvent; The initiator is a polar solvent.

2. The silicon-based negative electrode material according to claim 1, characterized in that The mass volume ratio of the silicon powder, sodium alginate, conductive agent, poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid, initiator and solvent is 7-8g: 1-2g: 1g: 920-960μL: 230-240μL: 70-115mL.

3. The silicon-based negative electrode material according to claim 1, characterized in that The thickness of the copper sheet is 18-22 mm, and the particle size of the silicon powder is 25-35 nm.

4. The silicon-based negative electrode material according to claim 1, characterized in that The conductive agent is a carbon black conductive agent.

5. The silicon-based negative electrode material according to claim 1, characterized in that The polar solvent includes one or more of ethanol, ethylene glycol and isopropyl alcohol.

6. The silicon-based negative electrode material according to claim 1, characterized in that The solvent includes water and / or ethanol.

7. A method for preparing the silicon-based negative electrode material according to any one of claims 1 to 6, characterized in that: The steps include: (1) mixing silicon powder, sodium alginate, a conductive agent, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid), an initiator, and a solvent to obtain a slurry; (2) The slurry is applied on a copper foil and dried to obtain the silicon-based negative electrode material.

8. The method for preparing a silicon-based negative electrode material according to claim 7, wherein: The mixing temperature in step (1) is 24-26° C., and the mixing time is 2-5 min.

9. The method for preparing a silicon-based negative electrode material according to claim 7, wherein: The drying temperature is 140-160° C., and the drying time is 2.5-3.5 hours.

10. Use of the silicon-based negative electrode material according to any one of claims 1 to 6 or the silicon-based negative electrode material prepared by the method for preparing the silicon-based negative electrode material according to any one of claims 7 to 9 in lithium-ion batteries.

Citation Information

Patent Citations

  • Conductive binder for cathode of silicon substrate lithium ion battery and preparation method thereof

    CN106129416A

  • Conductive polymer-coated silicon-based negative electrode material and preparation method thereof

    CN106229495A

  • Binder for lithium ion battery silicon-based anode and preparation method and application of the binder

    CN109411757A

  • PEDOT: PSS / CMC composite binder and preparation method and application thereof

    CN110890545A

  • Application of self-adaptive three-dimensional conductive binder in silicon-based lithium ion battery

    CN117525425A

Cited By

  • Negative plate, preparation method and battery

    CN122000291A

  • A method for preparing a silicon-based negative electrode of a lithium ion battery by using a Keggin structure polyoxometalate and application thereof

    CN122739259A